A first step design in integrating an English-Malay translation memory system into the semantic web - Ab. Rahman, Suhaimi (2008)
This paper discusses on the first step designing integration Semantic Web into our English-Malay Translation Memory (TM) prototype system.The main research activity that we need to perform is on how we can design and construct the ontology database in the architecture of the semantic web environment. Research also need to be carried out by understanding precisely the layer-cake architecture of semantic web, mainly in designing and implementation interaction between English-Malay TM system via a semantic web.